Pengaruh Variasi Waktu dan Larutan Elektrolit Terhadap Perubahan Massa Logam Selama Proses Anodizing Aluminium - Nabila Putri Rahayu; Silvi Busada; Umi Salamah; Yunella Eka Putri (Indonesian Chemical Connections Society, 2023)
This study examines the effect of time variation and electrolyte solution on metal mass changes during the aluminium anodizing process. The research investigates different anodizing durations and electrolyte concentrations to determine their impact on mass gain and surface quality. Results show that both time and electrolyte composition significantly influence the anodizing efficiency and coating thickness.